Psychogenic and behavior risks in postoperative period in maxillofacial surgery - Semenov, D. M.; Семенов, Денис Михайлович (My University, 2019)
Introduction. Maxillofacial trauma is one of the most relevant surgical issues in modern urban society. The issues of correction of post-traumatic pain and functional disorders, as well as prevention of psychological and behavioral violations in maxillofacial surgery patients creates specific interdisciplinary surgical and psychological problem. Aim – to systematize psychological and behavioral violations caused by stress associated with maxillofacial trauma and to evaluate its impact on postoperative treatment. Materials and methods. The study conducted in a prospective design during 2016-2018. 120 patients with maxillofacial area fractures, undergoing reconstructive surgery at City Clinical Hospital of Emergency and Rapid Care (Zaporizhzhya, Ukraine) were examined. Results. Predictors, psychological manifestations and influence on the in- and outpatient stages of the postoperative period of mixed negative emotional reactions on TAS; psychomotor reactions on TAS; somato-functional reactions on TAS; dental response on TAS; behavioral reactions on TAS; psychosensory reactions on TAS, personality reactions to changes in self-perception; personality reactions to social dysfunction; personality reactions to the violation of family status; personality reactions to communicative disorders; personality reactions to quality of life decrease; personality reactions to general condition violations; personality reactions to existential distress are described. Conclusions. Psychological and behavioral violations caused by stress associated with maxillofacial trauma are systematized, 6 main components of trauma-associated psychosocial maladaptation and 7 main components of defect-associated psychosocial maladaptation are described.
Keywords: maxilla-facial trauma; postoperative period; behavior; trauma-associated stress; defect-associated stress